2021
DOI: 10.1002/mgg3.1769
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Y chromosome microdeletion in azoospermia factor subregions among infertile men from West Bengal, India

Abstract: Infertility is a major challenge to reproductive health and the etiology involves both genetic and environmental risk factors. Approximately 15% of couples are infertile across the globe, and the origin of problems is shared almost equally by both the sexes (Poongothai et al., 2009). The problem of male infertility remains unaddressed in Indian society owing to male domination and illogical male chauvinism. Low sperm count is a clinically established cause of infertility among Indian

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
2
9
1
Order By: Relevance
“…Y chromosome microdeletion (YCMDs) is one of the major genetic causes of male infertility and it leads to the quantitative reduction of spermatozoa and causes spermatogenic failure [29][30][31]. We have analysed YCMDs of AZF sub-regions in this population in our previous study [32]. AZFc is a hotspot of structural mutations that cause signi cant spermatogenic impairment in nearly all males.…”
Section: Discussionmentioning
confidence: 99%
“…Y chromosome microdeletion (YCMDs) is one of the major genetic causes of male infertility and it leads to the quantitative reduction of spermatozoa and causes spermatogenic failure [29][30][31]. We have analysed YCMDs of AZF sub-regions in this population in our previous study [32]. AZFc is a hotspot of structural mutations that cause signi cant spermatogenic impairment in nearly all males.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the prevalence of AZFa microdeletions was higher in azoospermia patients than those with severe oligozoospermia. These findings were in agreement with the findings of Dutta et al 27 and in contrast with the results of Elsaid et al 26 Also, in line with our findings, Sha et al 28 from China, Asadi et al 30 from Iran, and Kim et al 31 from Korea, reported higher prevalence of AZFa microdeletions in patients with azoospermia than in those with oligozoospermia. Although in this study, AZFa microdeletion was found in both groups, but in previous studies from Egypt, 16 , 32 India, 27 China, 29 Iran, 30 and Korea, 31 it was identified only in the azoospermia patients, which was contrary to this research.…”
Section: Discussionsupporting
confidence: 93%
“…25 However, in a study from Sudan, the most frequent microdeletion was found in the AZFa region (11 out of 30 patients, 71.4%), followed by the AZFc ( n = 4) and the AZFb ( n = 3). 26 Dutta et al 27 from India found the AZFa microdeletions in 4.2% of infertile patients that was lower than our results.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations